Multinuclear NMR study of the complexes of 6-phospho-D-gluconic acid with W(VI) and Mo(VI) - Ramos, Luísa (2004)
Three and six complexes have been identified with tungstate and molybdate, respectively, in aqueous solution, depending on pH and concentration; the structure of an important species formed with Mo(VI) is shown.